Transplante interespecífico de espermatogônias-tronco de Brycon orbignyanus em Astyanax altiparanae (Teleostei: Characidae) - Silva, Diógenes Henrique de Siqueira [UNESP] (2015)
Germ cell transplantation is a recent approach which involves removal of undifferentiated germ cells from the donor gonads and transplantation into the gonads of a host, giving origin to sperm with genetic characteristics from the donor. Despite this methodology promising in studies involving initial germ cell biology, preservation of threatened species, reproductive biology and many other biotechnological approaches, the application of such a methodology in fish is still limited. Thus, the transplantation of spermatogonial cells from two phylogenetically related species piracanjuba Brycon orbignyanus into lambaris Astyanax altiparanae testis was histologically studied. Host spermatogenesis and urogenital papilla (transplantation via) were analyzed, highlighting nine spermatogonial generations and that each Sertoli cell supports the development of about 140 spermatids. Moreover, urogenital papilla is different between the sexes. For transplantation, piracanjuba's testes were enzymatic digested and spermatogonia were purified by a density gradient (Percoll), labeled with PKH26 and injected, through urogenital papilla, into lambaris testes, whose endogenous spermatogenesis had been previously suppressed by administration ofbusulfan (Myleran) associated with warm water (35°C) or by their maintenance at this temperature for longer time. About 66.67% and 84.6% of the host animals treated with busulfan + temperature and only temperature, respectively, presented cysts of donor germ cells into their epithelium. Spermatogonial transplantation involving B. orbignyanus and A. altiparanae was successfully performed and it can be applied in fish farms helping production increase and preservation of donor species piracanjuba (critically endangered), since donor spermatozoon can be obtained up to three weeks after transplantation process.